2010
DOI: 10.1037/a0018053
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national patterns of gender differences in mathematics: A meta-analysis.

Abstract: A gender gap in mathematics achievement persists in some nations but not in others. In light of the underrepresentation of women in careers in science, technology, mathematics, and engineering, increasing research attention is being devoted to understanding gender differences in mathematics achievement, attitudes, and affect. The gender stratification hypothesis maintains that such gender differences are closely related to cultural variations in opportunity structures for girls and women. We meta-analyzed 2 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

91
883
19
35

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,237 publications
(1,097 citation statements)
references
References 82 publications
91
883
19
35
Order By: Relevance
“…There are many different points of view, a fact which makes it a contested area (Kahle 2004;Penner 2008;Guo, Tsang, Ding 2010). Some of these studies have shown significant gender achievement gaps, with boys generally outperforming girls in Math and Science (O'Reilly, McNamara 2007;Penner 2008;Else-Quest, Hyde, Linn 2010) and girls excelling at literacy subjects. Others noted that these differences were not consistent.…”
Section: Gender and Academic Achievementmentioning
confidence: 99%
“…There are many different points of view, a fact which makes it a contested area (Kahle 2004;Penner 2008;Guo, Tsang, Ding 2010). Some of these studies have shown significant gender achievement gaps, with boys generally outperforming girls in Math and Science (O'Reilly, McNamara 2007;Penner 2008;Else-Quest, Hyde, Linn 2010) and girls excelling at literacy subjects. Others noted that these differences were not consistent.…”
Section: Gender and Academic Achievementmentioning
confidence: 99%
“…Over gender. Girls typically have lower MSCs than boys (Marsh, 1989;Else-Quest, Hyde & Linn, 2010) and these gender differences have been shown to generalize broadly over different countries in large cross-national studies such as PISA (OECD, 2015;Marsh, Hau, et al, 2006) and TIMSS (Goldman & Penner, 2014). Hence, it is reasonable to ask whether relations between MSC, MACH and effort vary as a function of gender.…”
Section: Robustness Of Path Coefficientsmentioning
confidence: 99%
“…The findings of the study can serve as an input to the national initiative to reduce gender gap in mathematics achievement (Korean Institute of Curriculum andEvaluation, 2008 &. Given there are limited studies of Asian countries (Else-Quest, et al, 2010;Lee & Lee, 2011;Shin, 2012) this study can provide additional insight on gender differences in mathematics achievement.…”
Section: ⅰ Introductionmentioning
confidence: 87%
“…If girls do not perceive value in mathematics education they will put less effort, and as a consequence their performances will be expected to be low (Bleeker & Jacobs, 2004). Else-Quest, et al (2010) using the TIMSS 2003 data identified also noted that gender differences in mathematics achievement were significantly correlated with gender differences in self-confidence in mathematics. For societies where boys are expected to pursue more technical careers and take more advanced mathematics courses, boys have more opportunities to develop confidence in mathematics and in return can establish a perpetual view that boys perform better in mathematics than girls (O'Connoer-Petruso and Miranda, 2004).…”
Section: Mathematics Attitude Of Studentsmentioning
confidence: 99%
See 1 more Smart Citation